Genetic diversity of influenza A(H1)pdm09 viruses, detected in Portugal since the 2009 pandemic - Pechirra, Pedro (2015)
The antigenic drift of circulating influenza viruses requires a continuous monitoring of their antigenic and genetic properties in order to detect any changes that may justify the selection of different vaccine candidates, as well as changes in antiviral recommendations. Since its emergence in 2009, A(H1)pdm09 viruses show a constant antigenic pattern. However, genetically, in the post pandemic seasons these viruses revealed an increasing diversity. From the 2009 pandemic until the end of the 2013/2014 season, the Portuguese NIC has detected 1214 influenza A(H1)pdm09 viruses in the scope of the Portuguese Influenza Surveillance Programme. 416 viruses were isolated and characterised antigenically by HI assays. The HA1 genetic characterisation was performed for 135 viruses. All A(H1)pdm09 revealed no antigenic diversity, being antigenically similar to the vaccine strain A/California/7/2009. In the pandemic season viruses showed a very small genetic diversity belonginig to genetic group 1 (A/Hong Kong/2212/2010). In the 2010/2011 season, Portuguese pandemic viruses showed some genetic diversity, being distributed by 3 genetic groups: 4 (A/Christchurch/16/2010), 5 (A/Astrakhan/1/2011) and 6 (A/St. Petersburg/27/2011). In the following 2011/2012 season, the only one A(H1)pdm09 virus detected, belonged to group 7 (A/St. Petersburg/100/2011). The pandemic viruses circulating in 2012/2013 belonged to this group and to the group 6 (subgroup 6C). Viruses detected in 2013/2014 clustered also into the group 6 (but into the subgroup 6B). Since its emergence in 2009, the majority of pandemic H1 viruses, was antigenically similar to the vaccine strain A/California/7/2009, however, in the studied period, the H1 pandemic viruses revealed an increasing genetic diversity. In Portugal, A(H1)pdm09 viruses represented different genetic groups in circulation over the 5 last seasons. The virological surveillance of influenza A(H1)pdm09 highlights the importance of the genetic characterisation to understand possible pathways of evolution and antigenic drift of these viruses.